Pengembangan Aplikasi Hebat Fluida Berbasis Android Untuk SMA Kelas XI Pada Materi Fluida Statis - Arum Wulandari; Siti Idayatun; Christi Umita Meyputri (Risenologi, 2021)
The rapid development of technology and information has not been fully utilized in education system. There needs the development of Interactive learning media that can increase students' learning motivation. The aims of this study is to develop learning media for android-based Hebat Fluida applications for high school class XI on static fluid material. This study uses the Research and development (R&D) method and the research model used is the DDD-E (Decide, Design, Develop, Evaluate) development model. This research was conducted with a feasibility test which has 3 aspects, the material aspect getting a percentage of 83,75%, the media aspect getting a percentage of 90%, and the language aspect getting a percentage of 85%. It can be concluded that the average percentage of the feasibility test of the media is 86,25%, which means it is very valid and suitable for use Hebat Fluida as a learning medium.